THE INFLUENCE OF POSITIVE EMOTION AND SALES PROMOTION ON IMPULSE BUYING IN SHOPEE CONSUMERS IN PONDOK GEDE DISTRICT - Wahib, Moh (Transpublika Publisher, 2024)
The rise of e-commerce in Indonesia has transformed consumer behavior, leading to a growing preference for online shopping. Shopee, a unique e-commerce platform, is experiencing rapid growth in the country, sparking an increase in impulse buying. Factors such as positive emotions and sales promotions are believed to drive impulse purchases. This study employs quantitative research methods to explore these phenomena. By surveying 100 respondents, it was found that positive emotions do not impact impulse buying among Shopee users in Pondok Gede District. However, sales promotions have a significant influence on impulse buying in the same area. When combined, positive emotions and sales promotions have a notable effect on impulse buying behavior among Shopee users in Pondok Gede District. The findings of this study suggest that while positive emotions may not directly lead to impulse buying on Shopee, the presence of sales promotions can significantly influence consumer behavior. This highlights the importance of marketing strategies that leverage both emotional appeal and promotional offers to drive impulse purchases among online shoppers in Indonesia. Furthermore, the rapid growth of e-commerce platforms like Shopee in Indonesia indicates a shift towards a more convenient and accessible shopping experience for consumers. As more Indonesians embrace online shopping, businesses will need to adapt their marketing tactics to cater to the changing preferences of their target audience.